The axis of local cardiac endogenous Klotho-TGF-β1-Wnt signaling mediates cardiac fibrosis in human. (November 2019) - Liu, Qinghua; Zhu, Lang-Jing; Waaga-Gasser, Ana Maria; Ding, Yan; Cao, Minghua; Jadhav, Shreyas J.; Kirollos, Sandra; Shekar, Prem S.; Padera, Robert F.; Chang, Yu-Chun; Xu, Xingbo; Zeisberg, Elisabeth M.; et al.
Abstract: Background: Cardiovascular fibrosis is a major contributor to cardiovascular disease, the primary cause of death in patients with chronic kidney disease (CKD). We previously reported expression of endogenous Klotho in human arteries, and that CKD is a state of Klotho deficiency, resulting in vascular calcification, but myocardial expression of Klotho is poorly understood. This study aimed to further clarify endogenous Klotho's functional roles in cardiac fibrosis in patients with underlying CKD. Methods and results: Human atrial appendage specimens were collected during cardiac surgery from individuals with or without CKD. Cardiac fibrosis was quantified using trichrome staining. For endogenous Klotho functional studies, primary human cardiomyocytes (HCMs) were treated with uremic serum from CKD patients or recombinant human TGF-β1. The effects of endogenous Klotho in HCMs were studied using Klotho-siRNA and Klotho-plasmid transfection. Both gene and protein expression of endogenous Klotho are found in human heart, but decreased Klotho expression is clearly associated with the degree of cardiac fibrosis in CKD patients. Moreover, we show that endogenous Klotho is expressed by HCMs and cardiac fibroblasts (HCFs) but that HCM expression is suppressed by uremic serum or TGF-β1. Klotho knockdown or overexpression aggravates or mitigates TGF-β1-induced fibrosis and canonical Wnt signaling in HCMs, respectively. Furthermore, co-culture of HCMs with HCFs increases TGF-β1-induced fibrogenic proteins in HCFs, but overexpression of endogenous Klotho in HCMs mitigates this effect, suggesting functional crosstalk between HCMs and HCFs. Conclusions: Our data from analysis of human hearts as well as functional in vitro studies strongly suggests that the loss of cardiac endogenous Klotho in CKD patients, specifically in cardiomyocytes, facilitates intensified TGF-β1 signaling which enables more vigorous cardiac fibrosis through upregulated Wnt signaling. Upregulation of endogenous Klotho inhibits pathogenic Wnt/β-catenin signaling and may offer a novel strategy for prevention and treatment of cardiac fibrosis in CKD patients. Highlights: Chronic kidney disease (CKD) is one of the major causes of death in USA and among the global burden of diseases About 50% of the CKD-related mortality has been associated with cardiovascular disease (CVD) Both endogenous Klotho gene and protein are indeed expressed in human heart, and exert effects locally The axis of local cardiac endogenous Klotho-TGF-β1-Wnt signaling mediates cardiac fibrosis in CKD patients Upregulation of endogenous Klotho may offer a novel strategy for prevention and treatment of cardiac fibrosis in CKD patients